Recovery of Interest in Enforcement Procedure in the Republic of Slovenia - Irena Merc (LeXonomica, 2021)
In Slovenian enforcement procedures, the principle of formal legality applies, so the enforcement court is bound by the enforceable title. The court must allow the enforcement of the claim as it follows from the enforceable title. The creditor also needs an enforceable title to claim interest. Interest arising from a Slovenian enforceable title shall be executed at the interest rate specified in Slovenian legislation. In the Republic of Slovenia, interest arising from a foreign enforceable title takes place at the interest rate determined by a foreign substantive provision. If the interest rate is determinable in a foreign enforceable title, the Slovenian Enforcement Court shall concretise the obligation by determining the interest rate determined by foreign law before issuing the writ of execution.Povzetek. V slovenskem izvršilnem postopku velja načelo formalne zakonitosti, zato je izvršilno sodišče vezano na izvršilni naslov. Sodišče mora dovoliti izvršitev terjatve, kot izhaja iz izvršilnega naslova. Upnik potrebuje izvršilni naslov tudi za uveljavljanje obresti. Obresti, ki izhajajo iz slovenskega izvršilnega naslova, se izvršujejo po obrestni meri, določeni v slovenski zakonodaji. V Republiki Sloveniji se obresti iz tujega izvršilnega naslova izvršujejo po obrestni meri, določeni s tujim materialnim predpisom. Če je obrestna mera določena v tujem izvršilnem naslovu, slovensko izvršilno sodišče pred izdajo izvršilnega naslova konkretizira obveznost tako, da določi obrestno mero, ki jo določa tuja zakonodaja.